LITERASI NUMERASI SISWA DALAM PEMECAHAN MASALAH TIDAK TERSTRUKTUR - Muhammad Rifqi Mahmud; Inne Marthyane Pratiwi (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to explore the numeracy literacy of students in ill-structured problem-solving on the matter of numbers. This study involved 34 students of the 4th grader in one Madrasah Ibtidaiyah in Bandung. The research approach used is qualitative with the case study method. The type of data collected is test results about ill structured problem-solving. The data were collected from tests, document analysis, and interviews. After that, the data were analysed using thematic analysis, while the validity of data using triangulation, member checking, and reflexivity. The results of the research showthat students' numeracy literacy in ill structured problem-solving are (1) students are able to solve ill structured problem in the context of daily life; (2) students are able to analyze the information obtained from the problem then use the interpretation analysis to predict and draw conclusions. The difficulties experienced by students are (1) the difficulty in understanding the problem; (2) lack of students' understanding of the prerequisite material; (3) the difficulty in developing a settlement strategy; and (4) the difficulty in drawing conclusions.